Chiral and water‐soluble poly(2‐oxazoline)s. Issue 3 (27th November 2012) - Luxenhofer, Robert; Huber, Stephan; Hytry, Julia; Tong, Jing; Kabanov, Alexander V.; Jordan, Rainer
Abstract We describe the synthesis and characterization of the first water‐soluble and chiral poly(2, 4‐disubstituted‐2‐oxazoline)s. While poly(2, 4‐dimethyl‐2‐oxazoline)s are water soluble up to 100 °C, aqueous solutions of poly(2‐ethyl‐4‐methly‐2‐oxazoline) exhibit a lower critical solution temperature. This is discussed in context with its constitutional isomers poly(2‐oxazoline)s and poly(2‐oxazine)s. Circular dichroism spectroscopy revealed strong Cotton effects, which are also responsive to temperature in aqueous solution. It is therefore hypothesized that structures, comparable to polyproline helices, are formed in aqueous solution. In contrast to polyproline, poly(2, 4‐disubstituted‐2‐oxazoline)s are highly water soluble and therefore represent very interesting pseudo‐polypeptides that may be useful to develop responsive biomimetic biomaterials. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013